PP.30 The Effect of Maternal Sublinical Hypothyroidism on the IQ of Children. (26th April 2013) - Murphy, N; Diviney, M; Donnelly, J; Cooley, S; Kirkham, C; Foran, A; Breathnach, F; Malone, F; Geary, M
Abstract : In our practise, pregnant women are not routinely screened or treated for subclinical hypothyroidism (SCH) Our objective was to compare the IQ of children whose mothers had been diagnosed with SCH antenatally with closely matched controls. In a previous study we screened 1000 healthy nulliparous patients for SCH. Those with overt hypothyroidism were treated, whereas those with SCH were contacted postnatally for paediatric follow-up. SCH (defined as reduced free T4 with normal TSH, or normal free T4 with raised TSH) was found in 4.6% (n = 46) All children underwent a formal neurodevelopmental assessment at age 7 to 8 years by a psychologist blinded to the original maternal thyroid status. From the cases, 23 mothers agreed to assessment of their children as well as 47 controls. The children in the control group had higher mean scores than those in the case group across Verbal Comprehension Intelligence, Perceptual Reasoning Intelligence, Working Memory Intelligence, Processing Speed Intelligence and Full Scale IQ. Statistical testing confirmed a statistically significant difference in IQ between the groups. This had a 95% confidence interval (.144, 10.330) Our results highlight significant differences in IQ of children of mothers who had unrecognised SCH during pregnancy. Our study size and design prevents us from making statements on causation but our data suggests significant public health implications in terms of routine thyroid screening in pregnancy. The results of prospective intervention trials to address a causative association will be vital to address this issue.